Wnt-5a Increases No and Modulates Nmda Receptor in Rat Hippocampal Neurons - Garcia Huidobro-Toro, J (2014)
Wnt signaling has a crucial role in synaptic function at the central nervous system. Here we evaluate whether Wnts affect nitric oxide (NO) generation in hippocampal neurons. We found that non-canonical Wnt-5a triggers NO production; however, Wnt-3a a canonical ligand did not exert the same effect. Co-administration of Wnt-5a with the soluble Frizzled related protein-2 (sFRP-2) a Wnt antagonist blocked the NO production. Wnt-5a activates the non-canonical Wnt/Ca2+ signaling through a mechanism that depends on Ca2+ release from Ryanodine-sensitive internal stores. The increase in NO levels evoked by Wnt-5a promotes the insertion of the GluN2B subunit of the NMDA receptor (NMDAR) into the neuronal cell surface. To the best of our knowledge, this is the first time that Wnt-5a signaling is related to NO production, which in turn increases NMDARs trafficking to the cell surface. © 2014 Elsevier Inc. All rights reserved.